2014
DOI: 10.1111/hdi.12142
|View full text |Cite
|
Sign up to set email alerts
|

Gender, low Kt/V, and mortality in Japanese hemodialysis patients: Opportunities for improvement through modifiable practices

Abstract: Guidelines have recommended single pool Kt/V > 1.2 as the minimum dose for chronic hemodialysis (HD) patients on thrice weekly HD. The Dialysis Outcomes and Practice Patterns Study (DOPPS) has shown that "low Kt/V" (<1.2) is more prevalent in Japan than many other countries, though survival is longer in Japan. We examined trends in low Kt/V, dialysis practices associated with low Kt/V, and associations between Kt/V and mortality overall and by gender in Japanese dialysis patients. We analyzed 5784 HD patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 21 publications
(40 reference statements)
2
47
0
2
Order By: Relevance
“…In Canada and other Europe, the patients with BFR ≥ 250 mL/min take about 98% of the HD patients [9]. However, in Japan, the patients with BFR ≥ 250 mL/min account for 18% and BFR prescribed usually 200 mL/min for a typical HD treatment [6,9]. …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In Canada and other Europe, the patients with BFR ≥ 250 mL/min take about 98% of the HD patients [9]. However, in Japan, the patients with BFR ≥ 250 mL/min account for 18% and BFR prescribed usually 200 mL/min for a typical HD treatment [6,9]. …”
Section: Discussionmentioning
confidence: 99%
“…Some investigators proposed that the use of low BFR in Japan may contribute the longer survival compared other countries because the lower BFR may help facilitate the maintenance of high rate of AVF. Some investigators suggest that the use of low BFR may contribute the longer survival by facilitating the maintenance of high rate of AVF [6,8]. On the contrary, other studies demonstrated that increased BFR is important for optimizing dialysis dose [2,5] and inadequate dialysis dose is associated with increased mortality [1].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations